Implementation of Integrated Traditional Healthcare Policy at the Traditional Health Clinic of Puskesmas Sawit - Anggiana Mawadda Putri; Dwi Linna Siswardany (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: The integration of traditional medicine into the primary healthcare system expands community access to services, functioning as both an alternative and a complement to conventional treatment while strengthening promotive and preventive efforts. In Indonesia, this initiative is supported by several regulations, including Ministry of Health Regulation Number 37 of 2017. Objective: This study aimed to describe the implementation of integrated traditional health service policies at the Traditional Medicine Clinic of Sawit Primary Health Center. Methods: A qualitative descriptive design with a case study approach was used. Data were collected through semi-structured interviews lasting 40–45 minutes and document review. The study involved eight informants, including the traditional health program manager at the Boyolali Regency Health Office, the Head of Sawit Primary Health Center, healthcare workers, and community members who used the service. Results: The findings showed that implementation of integrated traditional health services was not optimal. Key constraints included a shortage of competent traditional health personnel, the absence of a dedicated operational budget, and limited service hours. Conclusion: Improving implementation requires recruiting qualified traditional health workers, providing continuous training, allocating specific budgets, and adjusting service duration to enhance effectiveness, sustainability, equity, accessibility, and overall community health benefits outcomes.